2010
DOI: 10.1515/znc-2010-5-605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Silymarin as a Promising Radioprotector

Abstract: Silymarin, a purifi ed extract of seeds of Silybum marianum L. and well known for its hepatoprotective abilities, has been evaluated for inherent utility as a radioprotective agent. A fraction (INM-7035) was authenticated by characterizing the percentage composition of silybin A and B (39.9% and 57.4%). Free radical scavenging activities of INM-7035 against superoxide radicals (>68%), hydroxyl radicals (>33.75%), DPPH (67.2%), and ABTS (32.4%) were also evaluated. The fraction chelated (>30%) ferrous ions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…57 The radioprotective property of Podophyllum hexandrum fraction (REC-2006) in p53-carrying hepatoma cell line, perhaps mediated by cell cycle regulatory proteins 58 and free radical scavenging activity and radioprotection of Caesalpinia digyna extracts 59 has been reported. More recently, the radioprotective property of a seed extract of Silymarin, with INM-7035 as its bioactive constituent 60 and the radiation mitigating effect of hydro-alcoholic extract of Saraca indica (SIE) against mice exposed to whole body γ-radiation have also been reported. 61 The exact mechanism by which SCE protects against the genotoxic effects of radiation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…57 The radioprotective property of Podophyllum hexandrum fraction (REC-2006) in p53-carrying hepatoma cell line, perhaps mediated by cell cycle regulatory proteins 58 and free radical scavenging activity and radioprotection of Caesalpinia digyna extracts 59 has been reported. More recently, the radioprotective property of a seed extract of Silymarin, with INM-7035 as its bioactive constituent 60 and the radiation mitigating effect of hydro-alcoholic extract of Saraca indica (SIE) against mice exposed to whole body γ-radiation have also been reported. 61 The exact mechanism by which SCE protects against the genotoxic effects of radiation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin (10) is frequently used in treatment of liver diseases for protection of liver cells against lipid peroxidation and prevention of liver glutathione depletion (Valenzuela et al, 1989;Mira et al, 1994). Several investigations have reported that silymarin (10) alleviated irradiation-induced damage, including changes in nucleic acids and histone proteins, and inhibited radiation-induced free radical generation and lipid peroxidation (Gakova et al, 1992;Adhikari et al, 2010). Silymarin (10) treatment resulted in significant protection against radiation-induced hepatotoxicity in liver of rats by antioxidant and free radical scavenging properties of silymarin (10) (Ramadan et al, 2002).…”
Section: Silymarinmentioning
confidence: 99%
“…Approximately 95 percent of colorectal cancers are adenocarcinomas. Silymarin has already been evidentiated for its radioprotective efficacy both at in vitro and in vivo levels [2][3][4][5] . The anticancer effects of silymarin can be understood by various molecular mechanisms including blocking of carcinogenesis at different stages, such as initiation, promotion, and progression.…”
Section: Introductionmentioning
confidence: 99%